Reshaping Engineering Education Addressing Complex Human Challenges - Habbal, Fawwaz; Kolmos, Anette; Hadgraft, Roger G.; Holgaard, Jette Egelund; Reda, Kamar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book is dedicated to exploring methods and charting the course for enhancing engineering education in and beyond 2023. It delves into the idea that education, coupled with social connections, is indispensable for a more profound comprehension of the world and the creation of an improved quality of life. The book serves as a conduit for incorporating complex problem-solving into engineering education across various formats. It offers a structured approach for tackling complex issues, comparing an array of techniques for managing complexity within the realm of engineering education. Moreover, the book scrutinizes several complex case studies derived from the United Nation's Sustainable Development Goals. Additionally, it explores intricate problem-solving and curriculum change case studies specific to engineering education from Harvard University, the University of Technology Sydney, and Aalborg University. .
Introduction -- A Systems Approach to Addressing Human Challenges -- Design for Complexity -- New Competencies for Systems Thinking -- Towards a Comprehensive Pedagogy -- Teaching and Learning Strategies -- Generic Competencies -- Educational Transformation -- Engineers and Practice at Harvard -- Problem and Project-Based Learning at Aalborg -- Studios Reshape Engineering Curricula -- Invitation to Change.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Technical education; Educational sociology; Education, Higher; Teaching; Education -- Curricula; Engineering and Technology Education; Sociology of Education; Higher Education; Didactics and Teaching Methodology; Curriculum Studies